DIGITALIZATION MODEL TO ENHANCE THE QUALITY OF FAMILY IN INDONESIAN RURAL AREAS - Bonivasius Prasetya Ichtiarto; Faharuddin Faharuddin; Nurjaeni Nurjaeni (Journal of Rural Development and Applied Technology, 2024)
Based on 2020 Indonesian Population Census there are 270.2 million people are living in Indonesia, with 43.3 percent are living in rural areas. 70.72 percent of population is in productivity age (15-64), and it mean that Indonesia is in demographic deviden era. Rural development become main program of Indonesian Government since Village Law no 6/2014 by establishment Ministry of Villages, Disadvantages Region and Transmigration. Since 2015 there is around 400 trillion rupiah has been disburse to villages as a village fund. The main program of line ministries in Indonesia also focus on villages, such as Desa SDGs (Villages of SDGs), Desa Digital (Digitalized Villages), Desa Ramah Perempuan dan Anak (Women and Children Friendly Villages), Desa Ramah Lansia (Elderly Friendly Villages), Kampung Keluarga Berkualitas (Quality Family Villages) and so on. Unfortunately, some of programs sometimes did not take demographic data in its planning. This paper aim to explain how to integrate many ministries programs in villages by using Presidential Instruction No 3/2022 about The Quality Family Village (Kampung Keluarga Berkualitas: Kampung KB). It also will be described two initiatives; Demographic Information Systems, contain Siperindu, Dashboard Kampung KB and Population Data Warehouse (Rumah Data Kependudukan: Rumah Dataku.) and a Multi Dimentional Rural Development Model as a digitalization model that can be used to enhance the quality of family in Villages.